(untitled) (Philippines, 2007)
The book begins by discussing PIA and the three important aspects of identifying the poor, identifying and measuring the program impacts, and conducting PIA in the CGE modeling framework. The succeeding discussions are organized around the five different tools developed in this study.
Keywords: Poverty,Nghèo